2015
DOI: 10.18632/oncotarget.3432
|View full text |Cite
|
Sign up to set email alerts
|

AMPK-mediated energy homeostasis and associated metabolic effects on cancer cell response and resistance to cetuximab

Abstract: We previously reported that cetuximab, an EGFR-blocking antibody, inhibits cancer metabolism via downregulation of HIF-1α and reverses the Warburg effect in cancer cells. Here, we report that inhibition of HIF-1 transcriptional activity by cetuximab does not necessarily lead to successful inhibition of cell proliferation. In several head and neck squamous cell carcinoma (HNSCC) cell lines, we observed a pattern of oscillating decrease and increase of intracellular ATP level after cetuximab treatment, and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…The LIVE/DEAD cell viability assay kit (Life Technologies) was used to detect cell death as we recently described [30]. In brief, following treatment, cells were incubated with 4 µM calcein acetoxymethyl ester and 2 µM ethidium homodimer-1 together in a 37°C, 5% CO 2 incubator for 45 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The LIVE/DEAD cell viability assay kit (Life Technologies) was used to detect cell death as we recently described [30]. In brief, following treatment, cells were incubated with 4 µM calcein acetoxymethyl ester and 2 µM ethidium homodimer-1 together in a 37°C, 5% CO 2 incubator for 45 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for Western blotting was previously described [8,11]. The primary antibodies used for Western blotting and their sources were as follows: HIF-1α and SREBP-1c, BD Biosciences; T172-phosphorylated AMPK, AMPK, S79-phosphorylated ACC1, ACC1, ACC2, and FASN, Cell Signaling Technology; and β-actin, Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, we reported that inhibition of HIF-1 transcriptional activity by cetuximab does not always lead to successful inhibition of cell proliferation [11]. In human head and neck squamous cell carcinoma (HNSCC) cells, we observed that the response to cetuximab-mediated growth inhibition was linked to the activity status of the cell energy sensor AMP-activated protein kinase (AMPK).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(15,114,115). Even though mitochondrial respiration is identified as a predominant biologic function of PGC1a in cancer, a few studies also underscore PGC1a as a promoter of FAO and glucose-or glutaminederived lipogenesis in recent years (49,51,58).…”
Section: Conclusion and Further Perspectivesmentioning
confidence: 99%